Indonesia Islamic Banking Stability in The Shadow of Covid-19 Outbreak - Sintia Dewi Nur Ajizah; Agus Widarjono (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT:   The Covid-19 pandemic that has occurred in the world has harmed economies since 2020, especially Indonesia. Therefore, it is very important to study the impact of this pandemic on the stability of Islamic banking in Indonesia and examine potential signs of post-pandemic recovery. This study examines the stability of Islamic banking in Indonesia. Stability is measured using ROA and Z-score. The data in this study are panel data for Islamic Commercial Banks (BUS) and Islamic Business Units (UUS). The data used is quarterly data for 2016-2020. This study uses the Generalized Method of Moment (GMM). The results of this study are ROA for Assets, CAR, FDR, and Covid-19 do not affect profits. However, NPF and BOPO have a negative effect. Whereas on the Z-score for Assets, CAR FDR has a positive effect. NPF and BOPO harm the stability of Islamic banking, except for Covid-19. Lower efficiency and problematic financing reduce the stability of Islamic banking. In addition, the results of our analysis, based on profitability and financial stability during the quarterly period, Islamic banking was able to survive during the Covid-19 pandemic. This research implies that even though some variables do not significantly affect profits, Islamic banks must still pay attention to other variables, such as ROA, owned assets, CAR, FDR, and Covid-19 which are likely to have a large negative impact on the long term. Apart from that, Islamic banks must also maintain profits and stability to survive and compete with conventional banking amid the Covid-19 pandemic. Keywords: Generalized Method of Moment, Islamic Bank, Banking Stability, Return on   Assets, Z Score ABSTRAK:   Pandemi Covid-19 yang terjadi di dunia memberikan dampak negatif bagi perekonomian sejak tahun 2020, khususnya Indonesia. Oleh karena itu, sangat penting untuk mengkaji dampak pandemi terhadap stabilitas perbankan syariah di Indonesia dan mengkaji potensi pemulihan pasca pandemi. Penelitian ini mengkaji tentang stabilitas perbankan syariah di Indonesia. Stabilitas diukur menggunakan ROA dan Z-score. Data dalam penelitian ini adalah data panel untuk Bank Umum Syariah (BUS) dan Unit Usaha Syariah (UUS). Data yang digunakan adalah data triwulanan tahun 2016-2020. Penelitian ini menggunakan Generalized Method of Moment (GMM). Hasil penelitian ini adalah ROA untuk Aset, CAR, FDR, dan Covid-19 tidak berpengaruh terhadap keuntungan perbankan syariah. Namun NPF dan BOPO berpengaruh negatif. Sedangkan pada Z-score untuk Aset, CAR FDR berpengaruh positif. NPF dan BOPO berpengaruh negatif terhadap stabilitas perbankan syariah, kecuali Covid-19. Efisiensi yang lebih rendah dan pembiayaan bermasalah mengurangi stabilitas perbankan syariah. Selain itu, hasil analisis, berdasarkan profitabilitas dan stabilitas keuangan selama periode triwulanan, perbankan syariah mampu bertahan selama pandemi. Hasilnya  menunjukkan implikasi bahwa meskipun beberapa variabel tidak berpengaruh signifikan terhadap keuntungan, namun Bank Syariah harus tetap memperhatikan variabel lain, seperti ROA, Aset yang dimiliki, CAR, FDR, dan  Covid-19 yang kemungkinan akan terjadi dampak negatif yang besar dalam jangka panjang. Selain itu, Bank Syariah juga harus mampu menjaga keuntungan dan stabilitas agar mampu bertahan dan bersaing dengan perbankan konvensional di tengah pandemi. Kata Kunci: Generalized Method of Moment, Perbankan Islam, Stabilitas Keuangan, Return on Assets, Z Score   REFERENCES Abbas, F., Iqbal, S., & Aziz, B. (2019). The impact of bank capital, bank liquidity and credit risk on profitability in postcrisis period:"Ž A comparative study of US and Asia. Cogent Economics and Finance, 7(1).doi:10.1080/23322039.2019.1605683 Aliyu, S., & Yusof, R. M. (2016). International journal of economics and financial issues profitability and cost efficiency of islamic banks: a panel analysis of some selected countries. International Journal of Economics and Financial Issues, 6(4), 1736–1743. Alqahtani, F., & Mayes, D. G. (2018). Financial stability of islamic banking and the global financial crisis: Evidence from the Gulf Cooperation Council. Economic Systems, 42(2), 346–360.doi:10.1016/j.ecosys.2017.09.001 Arellano, M., & Bond, S. (1991). Some tests of specification for panel data: Monte carlo evidence and an application to employment equations. Review of Economic Studies, 58(2), 277–297.doi:10.2307/2297968 Barzani, K. F. (2020). Profitability and risk in Indonesian islamic banking: A dynamic panel data analysis [Universitas Islam Indonesia]. Retrieved from https://dspace.uii.ac.id/123456789/30611 Ben Mimoun, M. (2019). Islamic banking and real performances in a dual banking system: Evidence from Saudi Arabia. International Journal of Islamic and Middle Eastern Finance and Management, 12(3), 426–447.doi:10.1108/IMEFM-07-2018-0223 Berger, A. N., Boubakri, N., Guedhami, O., & Li, X. (2019). Liquidity creation performance and financial stability consequences of Islamic banking: Evidence from a multinational study. Journal of Financial Stability, 44, 100692.doi:10.1016/j.jfs.2019.100692 Blundell, R., & Bond, S. (1998). Initial conditions and moment restrictions in dynamic panel data models. Journal of Econometrics, 87(1), 115–143.doi:10.1016/S0304-4076(98)00009-8 Elnahass, M., Trinh, V. Q., & Li, T. (2021). Global banking stability in the shadow of Covid-19 outbreak. Journal of International Financial Markets, Institutions and Money, 72, 101322.doi:10.1016/j.intfin.2021.101322 Eng, T. S. (2013). Pengaruh NIM, BOPO, LDR, NPL, dan CAR terhadap ROA bank internasional dan bank nasional go public periode 2007 – 2011. Jurnal Dinamika Manajemen, 1(3), 153–167.doi:10.22437/jdm.v1i3.1473 Fakhruddin, Iwan dan Purwanti, T. (2015). Pengaruh rasio kesehatan bank terhadap kinerja keuangan bank periode 2010-2013. Jurnal Kompartemen, XIII(2), 116–131.doi:10.30595/kompartemen.v13i2.1768 Havidz, S. A. H., & Setiawan, C. (2015). Bank efficiency and non-performing financing (npf) in the indonesian islamic banks. Asian Journal of Economic Modelling, 3(3), 61–79.doi:10.18488/journal.8/2015.3.3/8.3.61.79 Horobet, A., Radulescu, M., Belascu, L., & Dita, S. M. (2021). Determinants of bank profitability in cee countries: Evidence from GMM panel data estimates. Journal of Risk and Financial Management, 14(7), 307.doi:10.3390/jrfm14070307 Ilhami, & Thamrin, H. (2021). Analisis dampak Covid 19 terhadap kinerja keuangan perbankan syariah di Indonesia. Jurnal Tabarru': Islamic Banking and Finance, 4(1), 37–45.doi:10.25299/jtb.2021.vol4(1).608 Kusumastuti, W. I., & Alam, A. (2019). Analysis of impact of CAR, NPF, BOPO on profitability of Islamic banks (year 2015-2017). Journal of Islamic Economic Laws, 2(1), 30–59.doi:10.23917/jisel.v2i1.6370 Lubis, K. A. (2013). Penerapan generalized method of moments pada persamaan simultan panel dinamis untuk pemodelan pertumbuhan ekonomi di Indonesia. Unpublished thesis. Institute Teknologi Sepuluh November. Thamrin, Liviawati, & Rita Wiyati. (2011). Analisis perbandingan kinerja keuangan bank umum sayriah dan bank umum konvensional serta pengaruhnya terhadap keputusan investasi. Pekbis Jurnal, 3(1), 406–412.doi:10.31258/pekbis.3.01.%p Maritsa, F. H. N., & Widarjono, A. (2021). Indonesian islamic banks and financial stability: An empirical analysis. Jurnal Ekonomi Dan Bisnis, 5(1), 71–87.doi:10.14421/EkBis.2021.5.1.1279 Pravasanti, Y. A. (2018). Pengaruh NPF dan FDR terhadap CAR dan dampaknya terhadap ROA pada perbankan syariah di Indonesia. Jurnal Ilmiah Ekonomi Islam, 4(03), 148-159.doi:10.29040/jiei.v4i03.302 Primadita, N. (2020). Analisis pengaruh murabahah, mudharabah, musyarakah, FDR, NPF dan BOPO terhadap kinerja perbankan syariah tahun 2011-2020. Syi'ar Iqtishadi: Journal of Islamic Economics, Finance and Banking. 4(2), 36-58. doi:10.35448/jiec.v4i2.9843 Raouf, H., & Ahmed, H. (2021). Risk governance and financial stability: A comparative study of conventional and islamic banks in the GCC. Global Finance Journal,52, 100599.doi:10.1016/j.gfj.2020.100599 Rashid, A., & Jabeen, S. (2016). Analyzing performance determinants: Conventional versus islamic banks in Pakistan. Borsa Istanbul Review, 16(2), 92–107.doi:10.1016/j.bir.2016.03.002 Rizvi, S. A. R., Narayan, P. K., Sakti, A., & Syarifuddin, F. (2020). Role of islamic banks in Indonesian banking industry: An empirical exploration. Pacific Basin Finance Journal, 62.doi:10.1016/j.pacfin.2019.02.002 Salike, N., & Ao, B. (2018). Determinants of bank's profitability: Role of poor asset quality in Asia. China Finance Review International, 8(2), 216–231.doi:10.1108/CFRI-10-2016-0118 Suryani. (2012). Analisis pengaruh financing to deposit ratio (FDR) terhadap profitabilitas perbankan syariah di Indonesia (rasio keuangan pada BUS dan UUS Periode 2008-2010). Economica: Jurnal Ekonomi Islam, 2(2), 153–170.doi:10.21580/economica.2012.2.2.854 Tahliani, H. (2020). Tantangan perbankan syariah dalam menghadapi pandemi Covid-19. Madani Syari'ah, 3(2), 92–113.doi:10.51476/madanisyari'ah.v3i2.205 Taurif, M., Otok, B. W., & Latra, I. N. (2014). Estimation of generalized method of moment in logistic regression model. Proceeding of Seminar Nasional Matematika, Universitas Jember:19 November. Page 167–174. Widarjono, A. (2020). Stability of islamic banks in Indonesia: Autoregressive distributed lag approach. Jurnal Keuangan dan Perbankan, 24(1), 40–52.doi:10.26905/jkdp.v24i1.3932 Widarjono, A., Mifrahi, M. N., & Perdana, A. R. A. (2020). Determinants of Indonesian islamic rural banks' profitability: Collusive or non-collusive behavior?. Journal of Asian Finance, Economics and Business, 7(11), 657–668.doi:10.13106/jafeb.2020.vol7.no11.657 Youssef, A. H., El-Sheikh, A. A., & Abonazel, M. R. (2014). Improving the efficiency of GMM estimators for dynamic panel models. Far East Journal of Theoretical Statistics ,47(2),171-189. Zarrouk, H., Ben Jedidia, K., & Moualhi, M. (2016). Is islamic bank profitability driven by same forces as conventional banks?. International Journal of Islamic and Middle Eastern Finance and Management, 9(1), 46–66.doi:10.1108/IMEFM-12-2014-0120